Noncoding RNAs in Alzheimer’s Disease - Idda, M. Laura (Wiley Interdiscip Rev RNA, 2018)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and the main cause of dementia among the elderly worldwide. Despite intense efforts to develop drugs for preventing and treating AD, no effective therapies are available as yet, posing a growing burden at the personal, medical, and socioeconomic levels. AD is characterized by the production and aggregation of amyloid β (Aβ) peptides derived from amyloid precursor protein (APP), the presence of hyperphosphorylated microtubule-associated protein Tau (MAPT), and chronic inflammation leading to neuronal loss. Aβ accumulation and hyperphosphorylated Tau are responsible for the main histopathological features of AD, Aβ plaques and neurofibrillary tangles (NFTs), respectively. However, the full spectrum of molecular factors that contribute to AD pathogenesis is not known. Noncoding (nc)RNAs, including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), regulate gene expression at the transcriptional and post-transcriptional levels in various diseases, serving as biomarkers and potential therapeutic targets. There is rising recognition that ncRNAs have been implicated in both the onset and pathogenesis of AD. Here, we review the ncRNAs implicated post-transcriptionally in the main AD pathways and discuss the growing interest in targeting regulatory ncRNAs therapeutically to combat AD pathology.